Dinâmica da comunidade arbórea de uma floresta semidecidual em Uberlândia, Minas Gerais - Silva, Mariana Resende (2006)
This study describes a tree community dynamics based in two successive surveys taken with a 14 years interval with the objective of analyzing changes that occurred in the community in the period. The study was carried out in a semideciduous forest area by using 50 plots of 10 m x 10 m, where all trees with GBH > 10 cm were sampled in 1990 and again in 2004. In 1990 there was registered a total of 95 species and 818 individuals, while in 2004, we registered 95 species and 866 individuals. The basal area of the first inventory was 14.43 m2 and in the second was 13.42 m2. The floristic composition changed but the number of species remained the same. The species that disappeared were Aspidosperma parviflorum, Byrsonima laxiflora, Casearia decandra, Guarea guidonea, Machaerium nictitans, Maprounea guianensis, Maytenus sp., Qualea dichotoma, Xylopia sericea and Zanthoxylum rhoifolium and new entries were Casearia gossypiosperma, Eugenia sp., Ficus sp., Machaerium stipitatum, Myrcia rostrata, Myrcia sp., Ocotea lanceolata, Ocotea percoriacea, Pavonia malacophylla, and Unonopsis lindmanii. The Shannon s diversity index was 4.05 nats.individual-1 and the Pielou s evenness 0.62 in 1990 and 3.72 nats.individual-1 and 0.57 in 2004. The mean annual mortality rate was 4.1% and the mean annual recruitment rate 4.5%. The species that contributed most for the mortality rate were Casearia grandiflora and Siparuna guianensis while for the recruitment were Siparuna guianensis and Trichilia pallida. Mortality and recruitment were higher in the first diameter class. For number of individuals the half life was 16.92 years, the time of duplication was 15.04 years, stability was 1.06 years and turnover was 15.98 years. Changes observed in the forest community between surveys indicates that this fragment is possibility still a adapting to the interference suffered with the fragmentation and isolation in relation to others semideciduous forest areas.